Performance analysis of a single-blade archimedes screw turbine for low-head micro hydro applications - Maulana, Muhammad Ilham; Syuhada, Ahmad; Yusmanizar, Yusmanizar; Asyqar, Muhammad Aufa (Jurnal Polimesin, 2025)
The need for efficient micro-hydro power generation systems for low head locations and the challenges of electrification in remote areas are increasing. The Archimedes Screw Turbine (AST) offers a simple and environmentally friendly technological solution; however, experimental studies on single-blade configurations with heads below 1 meter are limited. This study aims to evaluate the performance of a single-blade AST turbine through experimental testing at varying heads (0.7-1.0 meters) and flow rates (106-1035 L/min). The analyzed parameters include torque, mechanical power, and turbine efficiency, with the application of the Taguchi method for optimization of experimental design and reduction of the number of tests. Results show that flow discharge has a dominant influence on turbine performance compared to head, with the maximum power of 115.89 W and the highest efficiency reaching 68.72% under the condition of 1 meter head and 1035 L/min discharge. This study confirms that the single-blade AST turbine can function optimally at low head conditions and is worthy of further development for small-scale renewable energy systems in irrigation canals and other shallow flow sources.